Comparison of phenolic profiles, antioxidant capacity and relevant enzyme activity of different Chinese wheat varieties during germination. (December 2017) - Chen, Zhijie; Wang, Pei; Weng, Yan; Ma, Yan; Gu, Zhenxin; Yang, Runqiang
Abstract: Three typical Chinese wheat varieties have been studied monitoring their phenolic profiles, antioxidant capacity and relevant enzyme activity during germination. Results showed that free and bound phenolic contents significantly increased in germinated wheat and contributed to enhanced antioxidant capacity. Sumai188 showed the highest total phenolic contents and antioxidant capacity after 4-day germination. Ferulic acid and p -coumaric acid were most abundant in germinated wheat and mainly existed in the bound form. Meanwhile, the activated Phenylalanine ammonia-lyase could result in the phenolic accumulation and the activities of antioxidant enzymes peroxidase, catalase and ascorbate peroxidase were also enhanced in germinated wheat. Jimai 22 could be differentiated by bound sinapic acid in the early stage of germination compared with the other two varieties from principle component analysis. In addition, multiple linear regression studies led to the conclusion that ferulic acid contributed the most to the bound phenolic contents, bound DPPH and ABTS activities. Highlights: Enhanced FPC and BPC resulted in elevated antioxidant activities of germinated wheat. Ferulic and p -coumaric acid were most abundant phenolic acids in germinated wheat. Wheat varieties were differentiated by bound sinapic acid during early germination. Antioxidant enzymes were synchronous activated with PAL during wheat germination. Ferulic acid contributed the most to the BPC, bound DPPH and ABTS activities.